A gestão estratégica no terceiro setor: estudo de caso numa organização eclesiástica - Oliveira Júnior, Aristides da Rocha (2002)
This study has the objective to evaluate until which extent the adoption of the strategic planning by the Presbyterian Church of Manaus (IPM) expresses its effective fitting within the strategic management paradigm, whose ethos is the predominance of the instrumental-strategic rationality and the market-orientated logic in the managerial actions. It is assumed as a research initial hypothesis that the adoption of this technique by IPM represented an instrumental-strategic managerial action and a deliberated incorporation of market-orientated managerial parameters, strengthening some of the organizational studies¿ ultimate conclusions about the colonization of the third sector¿s organizations by the capitalist system logic. The research method foresees: (a) a bibliographical review about the themes ¿critical social theories¿, ¿strategic management¿, ¿third sector¿ and ¿religious organizations sociology¿; and (b) a case study at IPM, religious organization established at the state of Amazonas, branch of the Presbyterian Church of Brazil (IPB) and socially active according to religious aims and related (social care, cultural, etc.).